The effects of height and distance on the force production and acceleration in martial arts strikes - Bolander, R. P.; Pinto Neto, O.; Bir, C. A. (Journal of Sports Science & Medicine, 2009)
Almost all cultures have roots in some sort of self defence system and yet there is relatively little research in this area, outside of a sports related environment. This project investigated different applications of strikes from Kung Fu practitioners that have not been addressed before in the literature. Punch and palm strikes were directly compared from different heights and distances, with the use of a load cell, accelerometers, and high speed video. The data indicated that the arm accelerations of both strikes were similar, although the force and resulting acceleration of the target were significantly greater for the palm strikes. Additionally, the relative height at which the strike was delivered was also investigated. The overall conclusion is that the palm strike is a more effective strike for transferring force to an object. It can also be concluded that an attack to the chest would be ideal for maximizing impact force and moving an opponent off balance.